Formulation Development, Statistical Optimization, In Vitro and In Vivo Evaluation of Etoricoxib-Loaded Eucalyptus Oil-Based Nanoemulgel for Topical Delivery - Nabil A. Alhakamy; Sabna Kotta; Javed Ali; Md Shoaib Alam; Khaled M. Hosny; Rasheed A. Shaik; Basma G. Eid; Yassine Riadi; Hani Z. Asfour; Noha Ashy; Shadab Md (Applied Sciences, 2021)
Pain is a common distress in chronic inflammatory diseases, and etoricoxib (ETB) is frequently used in its management. It possesses fewer adverse effects when compared with other non-steroidal anti-inflammatory drugs (NSAIDs). In the present study, ETB-loaded nanoemulsion (ETB-NE) was formulated and optimized. Eucalyptus oil, Tween 20, and PEG 200 were chosen as the oil, surfactant, and co-surfactant, respectively. The formulation was optimized using the Box–Behnken design. The optimized ETB-NE contained oil, Smix, and water in concentrations of 11.5, 38, and 50% respectively. It had droplet size, polydispersity index, and zeta potential values of 179.6 ± 4.21 nm, 0.373 ± 0.02, and −10.9 ± 1.01 mV, respectively. The optimized ETB-NE sample passed the thermodynamic stability and dispersibility tests. Transmission electron microscopy confirmed the spherical morphology of the NE droplets. The ETB-NE showed a biphasic drug release pattern and released 85.3 ± 1.8% of ETB at 12 h. The ETB-NE was formulated into nanoemulsion gel (NEG) by using 1% carbopol 934. ETB-NEG was characterized for pH, viscosity, drug content, and percentage entrapment efficiency. During in vitro permeation studies, the apparent permeability coefficient value was 0.072 cm−2 h−1 for ETB-NEG, while it was only 0.047 cm−2 h−1 for the ETB gel. The skin histopathology study results confirmed that the ETB-NEG formulation was non-irritant and safe for topical use. The maximum possible analgesia observed for ETB-NEG was significantly high (p < 0.05) with a value of 47.09% after 60 min. Similarly, a formalin-induced acute inflammatory pain study in rats also demonstrated higher analgesia for the ETB-NEG, with % inhibition values of 37.37 ± 5.9 and 51.95 ± 4.4 in the acute and late phases, respectively. Further, ETB-NEG showed 78.4 ± 3.5% inhibition at 8 h in the in vivo anti-inflammatory testing by rat paw edema method. The ETB-NEG was found to enhance the in vivo analgesic and anti-inflammatory effects of ETB. The study results could stimulate further studies in this area for establishing a clinically successful NEG formulation of ETB.